Kepentingan Indonesia Dalam Kerjasama ACFTA-ASEAN Tahun 2010 - Nurhidayah, Nastainu; Pramono, Sugiarto (Kajian Hubungan Internasional, 2023)
ACFTA ASEAN is the cooperation of China or China with countries in an ASEAN region or countries under the Southeast Asian Region. With the establishment of ACFTA ASEAN member countries and China can simplify trade activities between the two. This research aims to find out why Indonesia supports ACFTA ASEAN cooperation in the national interest in the field of Politic, Economic, Ideology and Image in International Association. The theory used by the author is the Theory of the National Interest. This research method uses qualitative methods using a literature approach that generates secondary data from various sources as well as through case studies resulting from the implementation of the ACFTA program. The results in the study explained that ACFTA Cooperation is the existence of a political interest, economic interest, ideological interest and image interest in National Development.